ANALISIS HUBUNGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN SELF EFFICACY SISWA SMK - Fanny Mutia Suci Febrianti; Gida Kadarisma; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this research is to examine how the relationship between mathematical creative ability and self-efficacy of vocational students. The research method used in this research is correlational research, where the purpose of this research to see the relationship between two variables. Where the population is taken is all students of SMK on one SMK in Cmahi City, and taken a sample of one class. In the form of a test of creative thinking test in the form of a description of 5 questions and non-test in the form of self-efficacy questionnaire as many as 30 statements The Questionnaire Score is then transformed using Method of Successive Interval (MSI), then tested the correlation using Product Moment Pearson and Spearman. From the results of the study showed that there is a significant relationship between the ability of mathematical creative thinking and self-efficacy of students in learning mathematics